Protecting Famous Trademarks: Legal Insights from the EV Electro Voice Case in Indonesia - Robiyatul Adawiyyah, Inni Isnaini; Indrawati, Septi (Universitas Internasional Batam, 2024)
Trademark rights play a critical role in business, particularly in navigating global competition and safeguarding well-known brands. However, the principle of good faith in trademark registration is often exploited to mimic the fame of established trademarks. This study examines the prohibition of the registered trademark